Dynamic cooperative media access control for wireless networks‡. Issue 13 (3rd March 2014) - Cao, Bin; Li, Yun; Wang, Chonggang; Feng, Gang
Abstract Cooperative communications can obtain spatial diversity, high channel capacity, and reliable transmission without multiple antennas, and thus, it has become a hot topic in recent years. Different from existing research, this paper pays attention on cooperative media access control (MAC) mechanism, which considers both physical gain and MAC overhead caused by cooperation. To this end, a dynamic cooperative MAC mechanism for wireless networks, called DCMAC, is proposed. DCMAC can obtain the useful channel state information through broadcasting characteristic of wireless channel, choose the suitable helpers to relay data with our proposed helpers selection algorithm, and reserve wireless channel efficiently and dynamically. Numerical results show the effectiveness of DCMAC to improve the system performance.